Cohabitation and conflict in cohabiting termite species - Santos, Helder Hugo dos (2016)
In spite of behaving aggressively against nest intruders, termites are frequently found sharing their constructions with another termite species. Once in a single nest, cohabiting termites face the challenge to deal with conflicts that may arise from eventual encounters. An intriguing question is how cohabitation in such terms is even possible. Previous investigations have suggested that inquiline termites would adopt strategies to reduce frequency of encounter with their hosts. However, be- cause nests may be considered physical boundaries confining individuals in a single environment, it is plausible to suppose that in the long term host-inquiline encoun- ters would eventually take place and under these circumstances inquilines would be required to behave accordingly and prevent conflict. This prediction, however, has never been directly tested and little is known about what actually happens at host- inquiline encounters. Here we show that once inevitably exposed to hosts, inquiline termites tend to behave peacefully and weaken confront escalation, even when di- rect contact with opponents is already established. We found in focal ethograms that inquilines present low aggressiveness profile, interacting very little with hosts even under forced condition such as experimental arenas. We show different eva- sive manoeuvres performed by inquilines such as reverse, bypassing and an intricate mechanism using defecation to repel hosts, suggesting that active avoidance seems to be also in place. The set of behavioural adaptations we described may play an important role in cohabitation since it could improve chances of nest-sharing by hosts and inquilines without major problems.